Designing for diversity: Wetland ageing and habitat features at multiple scales influence the use of constructed wetlands by breeding waterfowl - Rawal, Prakhar; Laaksonen, Toni; Kačergytė, Ineta; Seimola, Tuomas; Väänänen, Veli-Matti; Lindén, Andreas (Elsevier, 2026)
Over the past few decades, Europe has made significant efforts to restore and construct wetlands to halt the ongoing habitat and biodiversity losses. These endeavours require considerable time, investment, and effort, making it crucial to ensure that they are highly effective in achieving their objectives, one of which is biodiversity conservation, including waterbirds. We monitored waterfowl communities at 146 constructed wetlands in unprotected landscapes across Finland. We studied the effects of habitat and landscape (at two spatial scales) variables on four breeding waterfowl metrics – species richness, pair abundance, brood abundance, and mean brood size. We also investigated how these metrics vary as wetlands age over time, and depending on gull populations. We found that wetlands with larger perimeters, more islands, and greater gull abundance supported higher species richness and more breeding pairs and broods. However, mean brood size was unexpectedly lower at wetlands with more islands. Pair and brood abundance peaked seven and four years after establishment, respectively, while species richness declined linearly with age. At the local scale (200 m), wetlands surrounded by more peat-associated elements and built-up cover had lower species richness and mean brood size, respectively. Brood abundance was higher in wetlands surrounded by broad-leaved forest at both the local and regional (2 km) scale, while regional marsh cover positively influenced species richness and pair abundance. Such findings provide valuable feedback on wetland construction and restoration projects, helping to ensure that future initiatives can improve their biodiversity conservation outcomes.
Keywords: created; artificial; man-made; landscape effects; waterbird; wetland bird